Penyusunan Company Profile Sebagai Wujud Branding Pariwisata Desa Hargorejo - Muhammad Eko Atmojo; Ahmad Syafiqurahman (Universitas Mathla'ul Anwar Banten, 2022)
PREPARATION OF COMPANY PROFILE AS A FORM OF TOURISM BRANDING IN HARGOREJO VILLAGE. Tourism is one of the most affected sectors amid the Covid-19 Pandemic. The existence of a policy that requires limiting tourism activities, turns out to have an impact on the development of tourism nationally in villages. One of them is Kalurahan Hargorejo, Kokap District, Kulon Progo Regency which has a variety of natural beauty that is geographically located in the hills of Mount Menoreh. The beautiful and interesting natural potential was utilized by the community and the Kalurahan Hargorejo Government to form a tourist village. The community service team found several problems starting from the inadequate management of the Village Information System (SID), institutional strengthening, and making a company profile video that functions as a promotional medium and tourism branding. the method of implementation used in this devotion starts from observation and execution/ execution. The results of community service include strengthening institutions focused on SID management by making the Kalurahan Hargorejo Government a partner. Then continued with the creation of village profile books and company profile videos as one of the means of tourism promotion. The results of the company profile video were made and published through Kalurahan Hargorejo's official YouTube and Instagram channels and uploaded to one of the well-known Instagram accounts, namely @Visitingjogja. This community service activity concludes that partners then have skills in managing and integrating village tourism information and managing social media as a forum for branding and promotion. In its implementation, partners still have some obstacles related to the lack of supporting tools such as cameras, clip-on, video editing, and so on. However, overall community service programs to strengthen tourism villages in Kalurahan Hargorejo can run well and sustainably.